2018
DOI: 10.1021/acs.joc.8b00170
|View full text |Cite
|
Sign up to set email alerts
|

The Application of 2-Benzyl-1,4-naphthoquinones as Pronucleophiles in Aminocatalytic Synthesis of Tricyclic Derivatives

Abstract: This study demonstrates an unprecedented reactivity of 2-substituted-1,4-naphthoquinones. By applying the principle of vinylogy, they have been employed as vinylogous pronucleophiles in the organocatalytic cascade reaction for the first time. This novel catalytic activation of 1,4-naphthoquinones enables access to carboannulated naphthalen-1(4 H)-one derivatives of biological importance. The site-selectivity and stereoselectivity of a process proved possible to control by the proper choice of reaction conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Initial experiment using cesium carbonate as the catalyst showed that the chemoselectivity of the reaction was problematic (Scheme ). The formation of two different by-products 4a (as a result of dimerization of 1a ) and 5a (as a result of oxidation of the benzylic position in 1a ) was observed (Scheme ). Furthermore, they proved inseparable from the main product 3a .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial experiment using cesium carbonate as the catalyst showed that the chemoselectivity of the reaction was problematic (Scheme ). The formation of two different by-products 4a (as a result of dimerization of 1a ) and 5a (as a result of oxidation of the benzylic position in 1a ) was observed (Scheme ). Furthermore, they proved inseparable from the main product 3a .…”
Section: Resultsmentioning
confidence: 99%
“…Silica gel (silica gel 60, 230−400 mesh, Fluka) was used for flash chromatography (FC). 2-Substituted 1,4-naphthoquinones 1a−1h 7,11 and 8,8-dicyanoheptafulvene 2 2b were synthesized according to literature procedures. General Procedure for the Synthesis of Compounds 3a−3i.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Albrecht developed an enantio‐ and diastereoselective entry to carboannulated naphthalene‐1(4 H )‐one derivatives 159 through a tandem addition/intramolecular aldol condensation starting from naphthoquinone 156 (Scheme 41 ). [98] A similar strategy by Wu and Chi that ends up with an intramolecular Mannich addition reaction served to prepare tetrasubstituted cyclohexene carbaldehydes 160 , [99] while Li, Cheng and coworkers described the enantioselective Michael addition reaction of dienolates from alkylidene oxindoles 137 to enals. [100] In this same context, Zanardi's group explored the reactivity of doubly unsaturated enolizable malononitriles against enals under dual activation of both nucleophile and electrophile.…”
Section: Catalytic Methodsmentioning
confidence: 99%